Diplomasi Pertahanan Indonesia-Prancis Tahun 2019-2023 - Alfianta Cesario Rizky Maulana; Sri Yunanto (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
The relationship between Indonesia and France in the context of defense has experienced significant growth, particularly in terms of military and defense industry cooperation. The primary focus of defense diplomacy between Indonesia and France includes the procurement of defense equipment, technology transfer, joint military exercises, and the development of regional defense capabilities. This study aims to analyze the role of defense diplomacy between Indonesia and France. The theories applied in this research are Defense Diplomacy and National Interest. The research employs a qualitative approach, utilizing data collection techniques such as interviews with key informants and literature studies derived from books, journals, government documents, and online media. The conclusions indicate that defense diplomacy between Indonesia and France during this period has successfully fostered closer and more strategic bilateral relations, although there remains room for further development in the future.